Sports business and the theory of multisided markets - Oliver Budzinski; Janina Satzer (Philipps-University Marburg, Faculty of Business Administration and Economics, 2008)
Despite still being younger than a decade, the theory of multisided market has offered numerous valuable insights for the analysis of non-ordinary industries in which a supplier serves two distinct customer groups that are indirectly interrelated by externalities. Examples include payment systems, matching agencies, commercial media and software platforms. However, professional sports markets have largely been neglected so far in this kind of research although they possess the characteristics of multisided markets. We contribute to filling this gap by describing the platform elements of professional suppliers of sports events and outlining problems where an application of this theoretical framework is likely to provide valuable insights and to add to the existing knowledge. Among these problems are integrative pricing strategies of sports clubs towards such different customer groups like attendees, broadcasters, sponsors, etc., including their welfare and antitrust implications, design decisions of sports associations in order to promote positive feedback loops among the customer groups as well as strategies to reinforce positive externalities among customer groups and alleviate negative ones.
Keywords: L83; L82; L13; M21; 330; sports economics; two-sided markets; multisided platforms; professional sports business; pricing strategies; broadcasting rights